9p+9=3-3p-6

Simple and best practice solution for 9p+9=3-3p-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9p+9=3-3p-6 equation:


Simplifying
9p + 9 = 3 + -3p + -6

Reorder the terms:
9 + 9p = 3 + -3p + -6

Reorder the terms:
9 + 9p = 3 + -6 + -3p

Combine like terms: 3 + -6 = -3
9 + 9p = -3 + -3p

Solving
9 + 9p = -3 + -3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '3p' to each side of the equation.
9 + 9p + 3p = -3 + -3p + 3p

Combine like terms: 9p + 3p = 12p
9 + 12p = -3 + -3p + 3p

Combine like terms: -3p + 3p = 0
9 + 12p = -3 + 0
9 + 12p = -3

Add '-9' to each side of the equation.
9 + -9 + 12p = -3 + -9

Combine like terms: 9 + -9 = 0
0 + 12p = -3 + -9
12p = -3 + -9

Combine like terms: -3 + -9 = -12
12p = -12

Divide each side by '12'.
p = -1

Simplifying
p = -1

See similar equations:

| x^3-5x-9x=-45 | | 2x-5(-6x-7)=-189 | | 3*y+1=0 | | 10-d=d-2 | | 2q=-2+3q | | x+28=46 | | 10+5s=7s-10 | | -3s-3=-2s | | 15+6*y=18 | | 4-4q=-5-7q | | Z+10z-10=9z+6 | | 4x^3+28x^2+48x=o | | 8+7w=9w-10 | | 7x+(-3x)=12+5x+(-2) | | -9h-9=-10h | | 7d-10=5d+8 | | 16x-2x^4=0 | | 5-24=x | | -w+202=79 | | 11-21x=7x-16 | | 75x^2=192 | | 236=-x+88 | | 11x-21=7x-6 | | 18=5g+3 | | 7x-10x=0 | | 3(2x-9)=3 | | 6x^3-84x^2+270x^2= | | -4x-7(x-3)=-100 | | 3k+9=5k+25 | | 7x-11=5x-7 | | 5m-35=6m+60 | | 45-7x+2x=100 |

Equations solver categories